Intruders at Rivermead Manor : a Kit mystery - Reiss, Kathryn (American Girl, 2014)
During the Great Depression, aspiring reporter Kit Kittredge uncovers a mystery surrounding a secret room in the rundown mansion owned by elderly Miss Mundis.